2020
DOI: 10.1371/journal.pone.0226182
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-specific CD8+ T-cell responses are associated with arterial blood pressure in people living with HIV

Abstract: People living with HIV (PLHIV) are at increased risk for cardiovascular disease (CVD), and immunity against cytomegalovirus (CMV) may be a contributing factor. We hypothesized that enhanced T-cell responses against CMV and CMV-IgG antibody-levels are associated with higher arterial blood pressure in PLHIV. We assessed serum CMV-IgG, systolic-(SBP) and diastolic-(DBP) blood pressure, pulse pressure (PP), traditional risk factors, activated CD8+ T-cells (CD38+HLA-DR+), senescent CD8+ T-cells (CD28-CD57+) and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…The associations between age-related telomere shortening and CAD as well as CVD-related mortality have already been investigated ( 255 257 ). In addition, structural alterations in biologically ageing arteries such as elastin fragmentation ( 258 ), collagen accumulation ( 259 ), decreased vascular compliance ( 260 ) and increased arterial stiffness ( 261 ) as well as elevated blood pressure ( 262 ) are reported as the consequence of chronic viral infections, too. Premature ageing may impose similar risks of developing CVDs in younger individuals.…”
Section: Drivers Of Immunosenescence and Atherosclerosismentioning
confidence: 99%
“…The associations between age-related telomere shortening and CAD as well as CVD-related mortality have already been investigated ( 255 257 ). In addition, structural alterations in biologically ageing arteries such as elastin fragmentation ( 258 ), collagen accumulation ( 259 ), decreased vascular compliance ( 260 ) and increased arterial stiffness ( 261 ) as well as elevated blood pressure ( 262 ) are reported as the consequence of chronic viral infections, too. Premature ageing may impose similar risks of developing CVDs in younger individuals.…”
Section: Drivers Of Immunosenescence and Atherosclerosismentioning
confidence: 99%
“…Moreover, Immunomic Therapeutics is collaborating with Dr. Duane Mitchell at the University of Florida on a Phase II proof of concept study using a pp65-lysosomal-associated membrane protein (LAMP)-based mRNA DC vaccine to treat patients bearing glioblastoma [730]. pp65 is a major cytomegalovirus (CMV) protein that provides exceptional tumor specificity for glioblastoma and is designed to stimulate pp65-specific CD4 + and CD8 + T cell response [731]. The previous phase I study showed a median overall survival of 35 months and progression-free survival of 31 months [731].…”
Section: Mrna Vaccine Encoding Tumor Associated Antigensmentioning
confidence: 99%
“…pp65 is a major cytomegalovirus (CMV) protein that provides exceptional tumor specificity for glioblastoma and is designed to stimulate pp65-specific CD4 + and CD8 + T cell response [731]. The previous phase I study showed a median overall survival of 35 months and progression-free survival of 31 months [731]. Table 13 highlights the different types of mRNA vaccines encoding tumor-associated antigens (TAAs) and their respective properties.…”
Section: Mrna Vaccine Encoding Tumor Associated Antigensmentioning
confidence: 99%